THE GITA AND MENTAL HEALING - Pathak, Rakesh Ranjan (Journal of Dharma, 1999)
Since Sigmund Freud, psychotherapy has undergone many tentative and ratified modifications. This article in its first half tries to establish a comparative superiority of the two-chair gestalt therapy, to which the Gita agrees essentially. The latter half of the article explains experimental validity of Gitaite mottoes apropos two-chair technique and other relevant researches.